Improvement of effect of water-in-oil microemulsion as an oral delivery system for fexofenadine: in vitro and in vivo studies - Gundogdu E (Dove Medical Press, 2011)
E Gundogdu1,2, I Gonzalez Alvarez3, E Karasulu1,21Faculty of Pharmacy, Department of Biopharmaceutics and Pharmacokinetics, 2Center For Drug Research and Development and Pharmacokinetic Applications, Ege University, Izmir, Turkey; 3Faculty of Pharmacy, Department of Engineering, Pharmaceutical Technical Section, Research Group on Drug Absorption, Universidad Miguel Hernández, Alicante, SpainAbstract: Fexofenadine (FEX) has high solubility and low permeability (BCS, Class III). In this work, novel FEX loaded water in oil microemulsion (w/o) was designed to improve bioavailability and compared with Fexofen® syrup in in vitro and in vivo studies. In addition, pharmacokinetic parameters in permeability studies were estimated by using WinNonLin software program. w/o microemulsion system was optimized using a pseudoternary phase diagram, composed of span 80/lutrol F 68 (9.5:0.5 w/w), oleic acide, isopropyl alcohol and water as surfactant mixture; oil and cosurfactant was developed for oral drug delivery. w/o microemulsion systems were characterized by phase behavior, particle size, viscosity and solubilization capacity. In vitro studies were studied using Caco-2 cell monolayer. Pharmacokinetic parameters of w/o microemulsion were investigated in rabbits and compared to Fexofen® syrup. Fexofen® syrup and microemulsion were administered by oral gavage at 6 mg/kg of the same concentration. The experimental results indicated that microemulsion (HLB = 5.53) formed nanometer sized droplets (33.29 ± 1.76) and had good physical stability. This microemulsion increased the oral bioavailability of FEX which was highly water-soluble but fairly impermeable. The relative bioavailability of FEX microemulsion was about 376.76% compared with commercial syrup in rabbits. In vitro experiments were further employed for the enhanced effect of the microemulsion for FEX. These results suggest that novel w/o microemulsion plays an important role in enhancing oral bioavailability of low permeability drugs.Keywords: pharmacokinetic, bioavailability, permeability, oleic acid